Assessing the Alignment of "English for Change" Textbook within the Merdeka Curriculum Framework - Ameliana, Ameliana; Zahro, Syifa' Khuriyatuz (Journal of Languages and Language Teaching, 2025)
With the introduction of the Merdeka Curriculum in the Indonesian educational system, new instructional materials were developed to support its implementation, including textbooks designed to align with the Curriculum's emphasis on global standards such as the Common European Framework for Reference for Languages (CEFR). Merdeka Curriculum-based textbooks require systematic evaluation to determine their alignment with both the Merdeka curriculum goals and CEFR proficiency levels. While existing studies do not focus on skill-specific material alignment with CEFR in English textbooks, this study fills a key gap by analyzing to what extent “Bahasa Inggris: English for Change” aligns with Merdeka Curriculum and the CEFR framework. This research aims to investigate the skill-specific alignment of the “Bahasa Inggris: English for Change” textbook for grade XI with the Merdeka Curriculum within the CEFR B1 framework. Using a descriptive qualitative content analysis approach and the adapted Tanto rubric, the textbook was evaluated across four language skills: listening, speaking, reading, and writing. The results indicate a high level of alignment, with overall 80% of the materials strongly conforming to CEFR B1 descriptors, and 20% showing moderate alignment with particular skills, such as reading, listening, and speaking. These results demonstrated that most of the specific-skill material in the textbook highly aligns with CEFR B1. This offers valuable insight for curriculum developers, textbook authors, and teachers by highlighting the alignment of textbook materials with both CEFR B1 and Merdeka Curriculum standards.